Factors Which Influenced on Two Years Recurrence of Epithelial Ovarian Cancer Patients After Surgery and Platinum Based Chemotherapy - SARI, RESTI MULYA (Indonesian Journal of Cancer, 2014)
Ovarian cancer was the leading cause of death in gynecologic cancer which had the two years recurrence rate of 50%. We used retrospective cohort design with survival analysis technique to examine the role of post-surgery residual tumor size, cancer cell histological subtype and cancer cell grading on epithelial ovarian cancer recurrence. We also want to know the prevalence of HER-2 (Human Epidermal Receptor-2) overexpression in epithelial ovarian cancer patients. Sixty-five epithelial ovarian cancer patient (1998-2012) who had achieved remission were observed for 24 months. We reported median age of 50 years with recurrence rate of 36.9% and mean time of first recurrence was 19.15 months. Size of post-surgery residual tumor more than 1 cm increase Hazard Ratio (HR) of two years recurrence of epithelial ovarian cancer with p value 0.02 and HR of 3.31 (95% CI 1.46-7.49) but papillary serous histology subtype and poor differentiated cancer cell grading did not influence the recurrence. One of 38 patients showed cytoplasmic staining in HER-2 overexpression examination by immunohistochemistry methods. Conclusion: Size of post-surgery residual tumor more than 1 cm increase Hazard Ratio of two years recurrence of epithelial ovarian cancer while papillary serous histology subtype and poor differentiated cancer cell grading did not influence the recurrence. One sample showed cytoplasmic staining on HER-2 overexpression examination.